Monetary policy and central banking : new directions in post-Keynesian theory - Rochon, Louis-Philippe.; Olawoye, Salewa 'Yinka. (Cheltenham : Edward Elgar, 2012)
The various contributors offer interesting and new perspectives on the conduct of monetary policy during the crisis, and provide sharp criticism of central bank policies in the US and Europe.
Includes bibliographical references and index.
oif 16/06/15
Loans
Keywords: Monetary policy; Banks and banking, Central